In vivo and in vitro anti-inflammatory activity evaluation of Lebanese Cannabis sativa L. ssp. indica (Lam.). (24th April 2021) - Shebaby, Wassim; Saliba, Jane; Faour, Wissam H.; Ismail, Jana; El Hage, Marissa; Daher, Costantine F.; Taleb, Robin I.; Nehmeh, Bilal; Dagher, Carol; Chrabieh, Edwin; Mroueh, Mohamad
Abstract : Ethnopharmacological relevance: Cannabis sativa L. is an aromatic annual herb belonging to the family Cannabaceae and it is widely distributed worldwide. Cultivation, selling, and consumption of cannabis and cannabis related products, regardless of its use, was prohibited in Lebanon until April 22, 2020. Nevertheless, cannabis oil has been traditionally used unlawfully for many years in Lebanon to treat diseases such as arthritis, diabetes, cancer and few neurological disorders. Aim of the study: The present study aims to evaluate the phytochemical and anti-inflammatory properties of a cannabis oil preparation that is analogous to the illegally used cannabis oil in Lebanon. Materials and methods: Dried Cannabis flowers were extracted with ethanol without any purification procedures to simulate the extracts sold by underground dealers in Lebanon. GC/MS was performed to identify chemical components of the cannabis oil extract (COE). In vivo anti-inflammatory effect of COE was evaluated by using carageenan- and formalin-induced paw edema rat models. TNF-α production were determined by using LPS-activated rat monocytes. Anti-inflammatory markers were quantified using Western blot. Results: Chemical analysis of COE revealed that cannabidiol (CBD; 59.1%) and tetrahydrocannabinol (THC; 20.2%) were found to be the most abundant cannabinoids.Various monoterpenes (α-Pinene, Camphene, β-Myrecene and D-Limonene) and sesquiterpenes (β-Caryophyllene, α-Bergamotene, α-Humelene, Humulene epoxide II, and Caryophyllene oxide) were identified in the extract. Results showed that COE markedly suppressed the release of TNF-α in LPS-stimulated rat monocytes. Western blot analysis revealed that COE significantly inhibited LPS-induced COX-2 and i-NOS protein expressions and blocked the phosphorylation of MAPKs, specifically that of extracellular signal-regulated kinase (ERK), c-Jun NH2-terminal kinase (JNK) and p38 MAPK. COE displayed a significant inhibition of paw edema in both rat models. Histopathological examination revealed that COE reduced inflammation and edema in chronic paw edema model. Conclusion: The current findings demonstrate that COE possesses remarkable in vivo and in vitro anti-inflammatory activities which support the traditional use of the Lebanese cannabis oil extract in the treatment of various inflammatory diseases including arthritis. Graphical abstract: Image 1